In search of safety : confronting inequality in women's imprisonment - Owen, Barbara A.; Wells, James, Ph.D; Pollock, Joycelyn M., 1956- (Gender and justice, 2017)
In Search of Safety takes a close look at the sources of gendered violence and conflict in women's prisons. The authors examine how intersectional inequalities and cumulative disadvantages are at the root of prison conflict and violence and mirror the women's pathways to prison. Women must negotiate these inequities by developing forms of prison capital-social, human, cultural, emotional, and economic-to ensure their safety while inside. The authors also analyze how conflict and subsequent violence result from human-rights violations inside the prison that occur within the gendered context of.